Olink proteomics analysis uncovers the landscape of inflammation-related proteins in patients with acute compartment syndrome - Wang, Tao; Yang, Shuo; Long, Yubin; Li, Yiran; Wang, Ting; Hou, Zhiyong (Frontiers in Immunology, 2023)
Abstract： Purposes: Our primary purpose is to explore the landscape of inflammation-related proteins, and our second goal is to investigate these proteins as potential biomarkers of acute compartment syndrome (ACS), which is a serious complication of tibial fractures. Methods: We totally collected serum from 15 healthy subjects (control group, CG) and 30 patients with tibial fractures on admission day, including 15 patients with ACS (ACS group, AG) and 15 patients without ACS (fracture group, FG). Ten samples in each group were analyzed by the inflammation panel of Olink Proteomics Analysis, and all samples were verified by ELISA. Receiver-operating characteristic (ROC) curve analysis was performed to identify the diagnostic ability and cut-off values of potential biomarkers. Results: Our findings showed that the levels of IL6, CSF-1, and HGF in FG were significantly higher than those in CG. Similar results were found between AG and CG and their cut-off values to predict ACS compared with CG were 9.225 pg/ml, 81.04 pg/ml, and 0.3301 ng/ml, respectively. Furthermore, their combination had the highest diagnostic accuracy. Notably, compared with FG, we only found higher expression of CCL23 in AG. Additionally, we identified 35.75 pg/ml as the cut-off value of CCL23 to predict ACS in patients with tibial fractures. Conclusions: We identified CCL23 as a potential biomarker of ACS in comparison with tibial fracture patients and the significance of the combined diagnosis of IL6, CSF-1, and HGF to predict ACS compared with healthy individuals. Furthermore, we also found their cut-off values, providing clinicians with a new method to rapidly diagnose ACS. However, we need larger samples to verify our results.